Designing Customer Analytics Dashboard in Smart Device Retail Using Power BI - Rahutomo, Reza (Journal of Information System and Informatics, 2025)
The adoption of data analytics has led to a paradigm shift in business decision-making, moving from intuition-based to data-driven strategies. Specifically in customer analytics, metrics such as Net Promoter Score (NPS), Customer Satisfaction Score (CSS), and Repeat Purchase Rate (RPR) are widely used to formulate customer retention strategies. Although dashboard applications like Microsoft Power BI support the visualization of these metrics, existing designs lack integrated filtering capabilities based on demographic characteristics such as gender and age group. This study aims to propose a Power BI dashboard application design that integrates NPS, CSS, and RPR with demographic filters to effectively convey customer loyalty, satisfaction, and advocacy. The research methodology includes four stages which are Power BI understanding, data acquisition, data pre-processing, and metric modeling. The dataset was collected by using an online questionnaire in January 2025 (N = 542). It must be validated and transformed before being modeled by using DAX. The proposed dashboard design offers an interactive interface, allowing users to explore insights through chart elements such as bars and pie slices. This design enhances user experience and supports intuitive analysis, making it a valuable tool for smart device retailers and manufacturers to make data-driven decisions. Additionally, the dashboard is adaptable to other business contexts with similar analytical needs. For real-world implementation, the inclusion of Key Performance Indicators (KPIs) for each metric is recommended to ensure that insights are actionable and aligned with business objectives.